Transmission blocking potency and immunogenicity of a plant-produced Pvs25-based subunit vaccine against Plasmodium vivax. Issue 28 (14th June 2016) - Blagborough, A.M.; Musiychuk, K.; Bi, H.; Jones, R.M.; Chichester, J.A.; Streatfield, S.; Sala, K.A.; Zakutansky, S.E.; Upton, L.M.; Sinden, R.E.; Brian, I.; Biswas, S.; et al.
Abstract: Malaria transmission blocking (TB) vaccines (TBVs) directed against proteins expressed on the sexual stages of Plasmodium parasites are a potentially effective means to reduce transmission. Antibodies induced by TBVs block parasite development in the mosquito, and thus inhibit transmission to further human hosts. The ookinete surface protein P25 is a primary target for TBV development. Recently, transient expression in plants using hybrid viral vectors has demonstrated potential as a strategy for cost-effective and scalable production of recombinant vaccines. Using a plant virus-based expression system, we produced recombinant P25 protein of Plasmodium vivax (Pvs25) in Nicotiana benthamiana fused to a modified lichenase carrier protein. This candidate vaccine, Pvs25-FhCMB, was purified, characterized and evaluated for immunogenicity and efficacy using multiple adjuvants in a transgenic rodent model. An in vivo TB effect of up to a 65% reduction in intensity and 54% reduction in prevalence was observed using Abisco-100 adjuvant. The ability of this immunogen to induce a TB response was additionally combined with heterologous prime-boost vaccination with viral vectors expressing Pvs25. Significant blockade was observed when combining both platforms, achieving a 74% and 68% reduction in intensity and prevalence, respectively. This observation was confirmed by direct membrane feeding on field P. vivax samples, resulting in reductions in intensity/prevalence of 85.3% and 25.5%. These data demonstrate the potential of this vaccine candidate and support the feasibility of expressing Plasmodium antigens in a plant-based system for the production of TBVs, while demonstrating the potential advantages of combining multiple vaccine delivery systems to maximize efficacy.